Sherebanglanagar : Louis Kahn and the making of a capital complex - Asraf, Kazi Khaleed (Loka Publications, 2002)
Collection of drawings and photographs on architecture of Dhaka, Bangladesh by Louis I. Kahn, 1901-1974; an exhibition held at Bangladesh National Museum, Dhaka from Aug. 17 - Sept. 9, 2002.